Motor learning - Applications for agility, part 2 - Jeffreys, I. (Strength and Conditioning Journal, 2006)
Part 2 of this 2-part article looks at how motor learning theories can be applied to the effective delivery of agility sessions. It also outlines an agility development system that can be used to construct a long-term development program for locomotive agility.